The Effect of Investment Motivation, Investment Knowledge, Return Perception And Brand Ambassador on Investment Interest In Hybe Corporation Stock (Survey on Followers of Bts Army Indonesia Social Media Account on Twitter) - Indah Khoiriyah; Nor Norisanti; Resa Nurmala (LP2M IAIN Palopo, 2025)
This study aims to analyze the influence of investment motivation, investment knowledge, return perception and brand ambassador on investment interest in Hybe Corporation shares, with the four variables having a significant effect on investment interest. This study uses a quantitative method with an associative approach, and involves 300 respondents selected through purposive sampling techniques. Data collection through questionnaires and literature studies. The results of the study indicate that investment motivation, investment knowledge, return perception and brand ambassador have a significant effect on investment interest, this is evidenced by the Tcount value being greater than Ttable. The implications of this study can be used as a basis for increasing investment interest through investment motivation, investment knowledge, return perception and brand ambassador among prospective investors.